Optimizing prophylactic antibiotic use among surgery patients in Ethiopian hospitals - Getachew Alemkere; Hailu Tadeg; Workineh Getahun; Wendosen Shewarega; Asrat Agalu; Mohan P. Joshi; Niranjan Konduri (Elsevier, 2023)
Background: Since 2018, the Ethiopian Ministry of Health (MOH) has been working to institutionalize antimicrobial stewardship (AMS) programs across the country. The US Agency for International Development Medicines, Technologies, and Pharmaceutical Services Program supported Ethiopia's multipronged One Health approach to combat AMR. The objective of this paper was to evaluate the effect of a quality improvement intervention to optimize the use of antimicrobials for surgical prophylaxis. Methods: Basic AMS interventions were introduced in five hospitals from January to May 2023. The AMS committees and multidisciplinary teams working at the surgical wards were trained and provided on-site support to implement surgical antibiotic prophylaxis (SAP) interventions. A before-after comparison was made for 206 medical records at baseline and 213 during the intervention phase. Qualitative data were gathered through discussions during experience-sharing workshops to supplement the quantitative results. Result: There were improvements in the presurgery dose of the prophylactic antibiotic and its timing: the doses within the recommended range increased from 11.2 % to 61.0 % (p < 0.001) and the optimal timing increased from 68 % to 82.6 % (p < 0.001). The hospitals also demonstrated some nonsignificant improvement in the duration of prophylactic antibiotic use (from 35 % to 44.6 % [p = 0.106]), with change in practice hampered by practitioners' resistance to early discontinuation for fear of infection due to perceived weaknesses in infection prevention and control practices. Nonavailability of the recommended antibiotic of choice for surgical prophylaxis was another major challenge in addressing all the elements of SAP. The intervention demonstrated a significant antibiotic-related average cost saving, 51.8 Ethiopian birr (∼1 US dollar) per patient (p = 0.028). Conclusion: Short-term investments with basic AMS interventions can help to improve SAP use in surgical wards. However, comprehensive success requires complementing AMS interventions with concurrent attention to proper supply chain and infection prevention and control.